O jogo educacional Codeland como instrumento de apoio ao ensino de lógica de programação com Python - Silva, Ayrtton Lucas; Nascimento, Gabriel da S.; Oliveira, Jhonatan Guilherme; Neto, Luiz Medeiros; Maria Edudarda Cunha Silva Araújo; Oliveira, Victor Andre Pinho de (Anais do Encontro de Computação do Oeste Potiguar ECOP/UFERSA (ISSN 2526-7574), 2023)
As students are being introduced to programming disciplines, some might have difficulties adapting to the teachers’ methodology. Very often, this stems from the fact that the teaching process used doesn’t suit all of the students. Thus, the purpose of this article is to show Codeland, a serious game under development with the objective of supporting logic and programming education with Python especially in higher education courses. Therefore, the game brings aspects like the ease of being applied in introductory programming disciplines and having exercises with the proposal of improving the thinking capacity of the students, being considered by the majority who tested it as an appropriate learning tool. Based on the ENgAGED development model, an initial version was developed with the MEEGA+ evaluation model being adopted so that students of introductory programming courses could validate it.